2016
DOI: 10.18805/lr.v0iof.10755
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, relative yield and plant growth of forage corn intercroppedwith soybean under different crop combination ratio

Abstract: An experiment was carried out to evaluate influence of different crop combination ratios of corn and soybean in terms of forage yield in corn-soybean intercropping. The experiment compared both corn and soybean as monocultures and in different intercropping ratios from 25:75, 50:50 and 75:25 of corn to soybean. The crop combination ratio had significant effects on physiological traits and dry matter yield of forage. The ratio of 75:25 and 50:50 recorded DM yields similar to those of monocropped corn (14.77 t/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Many studies have been reporting that intercropping soybean into maize did not affected maize biomass yield, showing similar or even higher values, what also resulted in silage with higher crude protein content Sánchez et al, 2010;Stella et al, 2016). Higher radiation use efficiency (RUE) (Liu et al, 2017;Gao et al, 2010;Baghdadi et al, 2016) and better soil use (Baghdadi et al, 2016;Yang et al, 2017) of intercrop versus monocrop support these results and turn out in better land equivalent ratio (LER) (Gao et al, 2010;Martin et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many studies have been reporting that intercropping soybean into maize did not affected maize biomass yield, showing similar or even higher values, what also resulted in silage with higher crude protein content Sánchez et al, 2010;Stella et al, 2016). Higher radiation use efficiency (RUE) (Liu et al, 2017;Gao et al, 2010;Baghdadi et al, 2016) and better soil use (Baghdadi et al, 2016;Yang et al, 2017) of intercrop versus monocrop support these results and turn out in better land equivalent ratio (LER) (Gao et al, 2010;Martin et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, Oliveira et al (1986) reported that maize-soybean intercropping resulted in higher DM yield in relation to the monocrop. Also, intercropping systems improved land use efficiency, once relative total yield (RTY) values of intercropping were higher than that of monocrop maize and soybean (Baghdadi et al, 2016).…”
Section: Total Biomass Yield (Maize+soybean)mentioning
confidence: 99%
“…Based on a research conducted by Gogoi et al (2015), a higher plant density was indicated to result in a greater number of plants per hectare compared to the treatment of a lower plant density. Intercropping system is able to increase production per unit of area and time and the intercropping system is also able to increase the efficiency of land use (Singh et al, 2010;Baghdadi et al, 2016).…”
Section: Fruit Weightmentioning
confidence: 99%
“…In the study, among different intercrop combinations studied, T 9 : maize + blackgram (2:2) recorded the maximum RYT (1.47) and it was followed by the treatment T 10 : maize + black gram at 2:2 row proportion. The higher RYT value with above treatments was probably made possible by the contribution of the legume to the environment of the maize via nitrogen fixation (Baghdadi et al 2016).…”
Section: Relative Yield Total (Ryt)mentioning
confidence: 93%